Perlindungan Hukum Terhadap Pekerja/Buruh Perusahaan dalam Mewujudkan Keselamatan dan Kesehatan Kerja di Kota Kendari - Arfa Arfa; Lade Sirjon; Yan Fathahillah Purnama; La Ode Muhammad Kaisar Demaq; La Patuju; Wahyu Aliansa; Muhamad Syukri (Proceedings Series on Social Sciences & Humanities, 2025)
This research focuses on the legal protection provided to workers and those responsible for ensuring occupational safety and health in Kendari City. This activity was conducted based on observations and media publications.onlinethat the number of workplace accidents in Southeast Sulawesi Province continues to increase annually. The implementation method for this activity is carried out using a literature study method and a case approach. The form of legal protection provided to workers/laborers in Kendari City is through preventive efforts in the form of monitoring and evaluation activities, and holding hearings, as well as repressive efforts in the form of clarification and mediation. Meanwhile, the parties responsible, authority and/or obligations in realizing occupational safety and health in Kendari City are the local government, employers/employers, workers/laborers, trade unions/laborers, employer associations and BPJS.